MARRIAGE AND ITS IMPACT ON WOMEN IN WILKIE COLLINS' THE WOMAN IN WHITE (1860): A FEMINIST APPROACH. - MUSTIAKANINGTYAS , DHIANITA (2010)
The major problem of this study is how marriage and its impact on woman in Wilkie Collins The Woman in white, especially viewed from feminist approach. The object of this study is the novel The Woman in White, which is giving emphases on the major character. The aim of the study is giving contribution to the body knowledge, particularly the literary study on Wilkie Collins The Woman in White. The technique of collecting data analysis is library research. In this study the writer uses two data sources, namely primary and secondary data. The primary data source is the novel itself and secondary data are the theory of Feminist, which is introduced by Simone de Beauvoir, and other books that are related to the research. The method of data collection is qualitative research. The results of the research are as follows. First, the analysis of structural elements of The Woman in White novel are connected to the each other to form unity. Second, The Woman in White is Wilkie Collins literary work that tell about Laura Fairlie who gets not good impact in her marriage. The last, Feminist analysis shows that woman cannot be man's equal. They cannot have all rights which are only intended for men such as right to speak. She cannot participate and have no role in public area.